The Impact of Café Lighting on Customer Comfort Perception: A Case Study of Threelogy Coffee and Zybrick Coffee and Cantina, Surabaya (International Journal of Architecture and Urbanism, 2024)
The evolution of cafés as multifunctional spaces for dining, socializing, and working has significantly influenced the standards for lighting. This study investigates the light intensity and customer comfort at Threelogy Coffee and Zybrick Coffee and Cantina, two cafés characterized by markedly different designs and lighting conditions. Field surveys and light intensity measurements were conducted to evaluate the lighting conditions at both locations, while questionnaires were used to assess visitor perceptions of comfort. At Threelogy Coffee, light intensity levels are notably high, with indoor measurements ranging from 360 to 465 lux and reaching up to 34,705 lux in semi-outdoor areas. This high level of illumination is attributed to natural sunlight and the reflective properties of white surfaces on ceilings and walls. Conversely, Zybrick Coffee and Cantina exhibits lower light intensity, with indoor levels between 65 and 70 lux and semi-outdoor areas ranging from 240 to 670 lux. This reduced illumination is due to limited natural light and the use of dark wall materials. Survey results reveal that customers to Threelogy Coffee generally express satisfaction with the bright lighting, although there is a potential risk of long-term monotony. In contrast, customers to Zybrick Coffee and Cantina report comfort despite the dim lighting, which is attributed to the private and intimate atmosphere fostered by the café's design. Both cafés exhibit comparable levels of overall comfort, highlighting the significance of atmospheric design elements, in addition to lighting, in creating a positive customer experience.